2021
DOI: 10.1016/s1473-3099(20)30493-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and molecular mapping of Pfkelch13 gene polymorphism in Africa in the era of emerging Plasmodium falciparum resistance to artemisinin: a systematic review

Abstract: The spread of Plasmodium falciparum isolates carrying mutations in the kelch13 (Pfkelch13) gene associated with artemisinin resistance (PfART-R) in southeast Asia threatens malaria control and elimination efforts. Emergence of PfART-R in Africa would result in a major public health problem. In this systematic review, we investigate the frequency and spatial distribution of Pfkelch13 mutants in Africa, including mutants linked to PfART-R in southeast Asia. Seven databases were searched (PubMed, Embase, Scopus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 88 publications
0
42
0
Order By: Relevance
“…Furthermore, with a relatively small number of antimalarials in use ( WHO Report on antimalarial efficacy, 2020 ) and the importance of ACTs to malaria control efforts in Africa, Pfk13 mutants should be closely and systematically monitored in Africa. Numerous studies have been published examining Pfk13 mutations across the continent ( Kamau et al, 2015 ; Kayiba et al, 2020 ). A recent study conducted by Uwimana et al (2020) , between 2012 and 2015 in Rwanda, highlighted the local emergence of an ART resistance validated mutation, R561H.…”
Section: Molecular Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, with a relatively small number of antimalarials in use ( WHO Report on antimalarial efficacy, 2020 ) and the importance of ACTs to malaria control efforts in Africa, Pfk13 mutants should be closely and systematically monitored in Africa. Numerous studies have been published examining Pfk13 mutations across the continent ( Kamau et al, 2015 ; Kayiba et al, 2020 ). A recent study conducted by Uwimana et al (2020) , between 2012 and 2015 in Rwanda, highlighted the local emergence of an ART resistance validated mutation, R561H.…”
Section: Molecular Epidemiologymentioning
confidence: 99%
“…Recently, a systematic review identified Pfk13 mutations across Africa that have been associated with ART resistance, though at low frequencies ( Kayiba et al, 2020 ). Here we present data of Pfk13 propeller domain mutations from >70 studies based on the PRISMA guidelines ( Fig.…”
Section: Summary Of the Pfk13 Mutations From The Extracted Literaturementioning
confidence: 99%
“…Since African pfk13-propeller mutations were shown to be different from those found in Southeast Asia, further molecular and biochemical studies should investigate whether other factors such as additional mutations could be associated with altered functions of the PFK13 protein, resulting in altered ART sensitivity. However, some of the validated and candidate mutations associated with ART resistance in Southeast Asia have been detected in the DRC [11,26] and in some neighbouring countries, such as Rwanda [8,9] and Uganda [10], providing evidence of de novo emergence of ART resistance in sub-Saharan Africa. Thus, surveillance must be strengthened to avoid the worst.…”
Section: Discussionmentioning
confidence: 99%
“…These mutations have spread within the Greater Mekong Subregion of Southeast Asia and have been classified as validated markers and candidate/associated markers of ART resistance [7]. Some of these mutations are increasingly being detected in sub-Saharan African countries, providing evidence for de novo emergence of resistance to artemisinin in Africa [8][9][10][11]. Mutations in the chloroquine resistance transporter gene (pfcrt) originally identified as a marker of CQ resistance, have also been associated with resistance to amodiaquine (AQ) [12].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, F446I yielded no significant in vitro resistance in 3D7 parasites, although similar to our data this mutation was fitness-neutral (Siddiqui et al ., 2020). Of note, all four of these mutations, and others including C469Y, R622I and A675V, have now been detected in Africa and merit gene editing experiments in African strains (Warsame et al ., 2019; Asua et al ., 2020; Kayiba et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%